A patient and public involvement (PPI) review exploring patient reported outcome measures in adult CAR T-cell therapy patients - Nikoletta Mama; Brittany Cucchiaro; Adrian Slee (Clinical Nutrition Open Science, 2023)
Summary: Background & Aims: Chimeric Antigen Receptor (CAR) T-cell therapy is a novel anti-cancer treatment option for patients with refractory or relapsed haematological malignancies. Preliminary research shows a significant proportion of patients receiving CAR T-cell therapy develop malnutrition and cachexia during treatment, with these nutritional issues associated with adverse patient outcomes. There is a lack of literature and no specific validated measures on patient experience and burden of symptoms for CAR T-cell therapy patients as well as the importance of clinical outcomes for these patients. Patient and public involvement (PPI) is a fundamental feature of proper research execution as it informs issues in the research that are most important in patients. The aim of this review was to identify priority patient-reported outcome measures in CAR T-cell therapy patients using PPI, in addition to exploring patient experiences, burden of symptoms, priorities, and knowledge of nutritional priorities in cancer. The PPI outcomes will also aid to inform the design and development of a future novel cohort study. Methods: Using participatory research (PPI), six adults aged 26–70 years who have received CAR T-cell therapy in the past two years, participated in one-to-one interviews. The interview questions were focused on the aims of identifying patient recommendations regarding clinical outcome measures of interest, their relevance to patient's experience of CAR T-cell therapy, and optimal design of the future cohort research protocol. Results: Eight main themes were identified through the interviews: unfamiliarity of terms malnutrition and cachexia; weight loss during treatment not considered a main concern; exercise deemed a main priority in all participants; fatigue as the main side effect; importance of survival, psychosocial concerns; nutritional supplementation issues and dissatisfaction in hospital food. Conclusions: The responses have revealed that the themes of exercise, fatigue, intensity of side effects and survival were deemed as highly important in all participants. In addition, consideration should be placed on the psychosocial concerns of participants in the future cohort study regarding assessments that may have higher patient burden, such as indirect calorimetry and body composition assessments. Moreover, reports regarding nutritional supplementation along with hospital meals provided during treatment, have shown that they are not fulfilling the participants' satisfaction and priorities. Future research undertaken in the novel area of CAR T-cell therapy should take measures to focus on these outcomes of importance to participants, to minimise burden and provide adequate support.